The Physiology Constant Database of Teen-Agers in Beijing - Wei-Qi, Wei (ScientificWorldJournal, 2004)
Physiology constants of adolescents are important to understand growing living systems and are a useful reference in clinical and epidemiological research. Until recently, physiology constants were not available in China and therefore most physiologists, physicians, and nutritionists had to use data from abroad for reference. However, the very difference between the Eastern and Western races casts doubt on the usefulness of overseas data. We have therefore created a database system to provide a repository for the storage of physiology constants of teen-agers in Beijing. The several thousands of pieces of data are now divided into hematological biochemistry, lung function, and cardiac function with all data manually checked before being transferred into the database. The database was accomplished through the development of a web interface, scripts, and a relational database. The physiology data were integrated into the relational database system to provide flexible facilities by using combinations of various terms and parameters. A web browser interface was designed for the users to facilitate their searching. The database is available on the web. The statistical table, scatter diagram, and histogram of the data are available for both anonym and user according to queries, while only the user can achieve detail, including download data and advanced search.